How successful are exchange rate communication and interventions? Evidence from time-series and event-study approaches - Marcel Fratzscher (European Central Bank (ECB), 2005)
The paper analyses whether communication and actual interventions in FX markets are successful in moving exchange rates over the medium- to long-run. It compares empirical evidence based on time-series analysis with that obtained from an eventstudy approach. Both the time-series approach based on option contracts and the event-study methodology yield compelling evidence that communication and actual interventions tend to be successful in moving exchange rates in the desired direction contemporaneously as well as over the medium- to long term. This finding is consistent with recent work on microstructure models that emphasises the importance of dynamic effects of news and fundamentals on exchange rates.
Keywords: C23; E41; E52; 330; communication; euro area; event-study methodology; exchange rate; intervention; Japan; policy; time-series analysis; United States; Wechselkurs; Wechselkurspolitik; Zeitreihenanalyse; EU-Staaten; Japan; USA